Estudo da passagem de diferentes concentrações de ácido fosfórico através da dentina e observação da morfologia dentinária pelo microscópio eletrônico de varredura - Badini, Sérgio Ricardo Garcia [UNESP] (1997)
The purpose of this study was to verify acid penetration of phosphoric acid at variable concentrations, into deep dentin, located at 0,3 mm from the pulp chamber, and a.tso observe dentin morphological changes with S.E.M. Occlusal dentin of human sound molars and premolars was exposed totaling 72 specimens. A special designed device was used to section teeth, obtaining 0.3 mm of remaining dentin over pulp horns. Teeth were randomly assigned to six groups with ten teeth each: group 1 - Control (no acid conditioning); group 2 - 10 % phosphoric acid: group 3 - 32 % phosphoric acid; group 4 - 35 % phosphoric acid with silica; group 5 - 37 % phosphoric acid; group 6 - 50 % phosphoric acid solution. A pH indicating paper was placed on pulp chamber walls in order to verify acid penetration of acid etchants. Each etchant was applied for 15 seconds, spray rinsed and air dried Conclusions: a) no acid penetration occurred through dentin; b) dentin tubules were partially open in crosscut 10 % phosphoric acid specimens; c) similar morphological changes were found for 50 % solution, 37 %, 35 % and 32 % phosphoric acid groups; d) most structural removal occurred at peritubular dentin; e) silica from 35% acid gel was not completely removed from dentin surface after thorough rinsing.